Graft survival after percutaneous transluminal renal stenting for transplant renal artery stenosis (TRAS) is worse compared to matched cadaveric grafts without TRAS - Long Zhang; Jilin Zou; Jiangqiao Zhou; Tao Qiu; Chenyang Kong; Tianyu Wang; Zhongbao Chen; Xiuheng Liu (Renal Failure)
Objectives Transplant renal artery stenosis (TRAS) is now recognized as a curable disease with a good prognosis if intervention occurs in the early stage. However, the mid-term outcomes of TRAS when treated by percutaneous transluminal angioplasty with stent placement have yet to be fully elucidated. The purpose of this study was to compare mid-term graft and patient survival of TRAS group with a control group.Patients and methods Ninety-two patients were diagnosed of TRAS between January 2016 and January 2022 in our center. Fifty-six pairs of recipients with grafts from the same donor were selected as a study group with TRAS and a control group without TRAS, respectively. All donor kidneys were from deceased organ donation rather than living donors. The primary endpoints were graft and patient survival. The secondary outcomes were changes in renal graft function.Results The mean follow-up time for the TRAS group was 43.6 months, while the mean follow-up time for the control group was 45.3 months. In the TRAS group, the age of patients ranged from 11 to 62 years with 39 males and 17 females. In the control group, the age of patients ranged from 18 to 67 years with 40 males and 16 females. In the TRAS group, there were more patients with diabetic nephropathy as the primary renal disease compared to the control group (5/56 vs 0/56), and the incidence of acute rejection was higher in the TRAS group than in the control group (12/56 vs 3/56). Eight patients in the TRAS group and one patient in the control group experienced graft loss (p = .019). Four patients in the TRAS group and four patients in the control group died with functional renal allograft during the follow-up time (p = .989). The levels of eGFR did not differ significantly between the two groups in the first three years after kidney transplant (p > .05). Patients in the TRAS group had worse graft functionality (eGFR, 44.96 ± 18.9 vs 54.9 ± 19.6 mL/min) in the fourth year when compared with the control group (p = .01).Conclusions The graft function deteriorated faster, and graft survival was lower in the TRAS group treated by stent placement when compared with a control group without TRAS over the mid-term.